Directed disruption of IL2 aggregation and receptor binding sites produces designer biologics with enhanced specificity and improved production capacity - Amy Dashwood; Ntombizodwa Makuyana; Rob van der Kant; Arman Ghodsinia; Alvaro R. Hernandez; Stephanie Lienart; Oliver Burton; James Dooley; Magda Ali; Lubna Kouser; Francisco Naranjo; Matthew G. Holt; et al. (Computational and Structural Biotechnology Journal)
The pleotropic nature of interleukin-2 (IL2) has allowed it to be used as both a pro-inflammatory and anti-inflammatory therapeutic agent, through promotion of regulatory T cell (Treg) responses via the trimeric IL2RABG receptor or promotion of CD8 T cell responses via the dimeric IL2RBG receptor, respectively. However, the utility of IL2 as a treatment is limited by this same pleiotropy, and protein engineering to bias specificity towards either Treg or CD8 T cell lineage often requires a trade-off in protein production or total bioactivity. Here we use SolubiS and dTANGO, computational algorithm-based methods, to predict mutations within the IL2 structure to improve protein production yield in muteins with altered cellular selectivity, to generate combined muteins with elevated therapeutic potential. The design and testing process identified the V106R (murine) / V91R (human) mutation as a Treg-enhancing mutein, creating a cation repulsion to inhibit primary binding to IL2RB, with a post-IL2RA confirmational shift enabling secondary IL2RB binding, and hence allowing the trimeric receptor complex to form. In human IL2, additional N90R T131R aggregation-protecting mutations could improve protein yield of the V91R mutation. The approach also generated novel CD8 T cell-promoting mutations. Y59K created a cation-cation repulsion with IL2RA, while Q30W enhanced CD8 T cell activity through potential π-stacking enhancing binding to IL2RB, with the combination highly stimulatory for CD8 T cells. For human IL2, Y45K (homolog to murine Y59K) coupled with E62K prevented IL2RA binding, however it required the aggregation-protecting mutations of N90R T131R to rescue production. These muteins, designed with both cellular specificity and protein production features, have potential as both biological tools and therapeutics.